Foreign Direct Investment and Manufactured Export Performance in India - Prasanna, N. (Indian Journal of Finance, 2011)
Export success among developing countries has been concentrated only in a few countries due to the fact that the comparative advantage of most of the developing countries still lies traditionally in primary commodities and unskilled-labour-intensive manufactures. For export success, these countries have to upgrade their primary and labour-intensive exports into higher value-added items, and move into new, more advanced, export-oriented activities. Both require greater inputs of skill and technology which could be achieved in several ways: by improving and deepening the capabilities of domestic enterprises or by attracting Foreign Direct Investment (FDI) into export activities and upgrading these activities over time. Recently, a much optimistic view on the role of FDI on export performance in the host country has evolved, which was also acknowledged by the Government of India in 1991 through a liberal FDI policy framework which in turn led to a phenomenal rise in the FDI inflows into India. Viewing this increasing trend of FDI inflows into India, this study explores the impact of FDI inflows on the manufactured exports in India. This study finds that the impact of FDI inflows on manufactured exports is significantly positive. The study also suggests that the policy regarding domestic efforts to enhance manufacturing exports needs reassessment in line with the FDI policy framework in order to reap maximum and long-term benefits.